Soil-landscape relationships at the Quadrilátero Ferrífero in the state of Minas Gerais, Brazil - de Carvalho Filho, Amaury; Curi, Nilton; Shinzato, Edgar (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was characterize the soils of a typical area of the Quadrilátero Ferrífero, Minas Gerais, Brazil, and to evaluate the relationships between these soils and the main components of the natural ambience. Seven distinct landscape units were identified – Depressão do Paraopeba, Serras Itabiríticas, Platô da Moeda, Vale do Rio das Velhas, Gandarela, Vale do Conceição, Serra do Caraça – whose aspects related to soils and their relationships with the components of the natural ambience were described. Under the influence of a great lithologic variability, in connection with a large period of geomorphologic evolution, the region is marked by strong topographic contrasts. There is a dominance of young soils (Cambisols and Litholic Neosols), showing low natural fertility, despite the marked differentiation of native vegetation, represented by tropical grassland formations side by side to the forest. In some areas, rocky outcrops are outstanding. The influence of the parent material on soil characteristics is remarkable, especially on the soil groups related to iron rocks, which are discernible by their very high iron oxide contents and their intense red color. The presence of ferruginous concretions is also very common in this soils. The occurrence of perferric soils (Oxisols), without coarse fragments, is associated to the pediment formation at the Serras Itabiríticas vicinity.
Keywords: ferriferous rocks; concretionary soils; perferric soils; tropical soils